2021
DOI: 10.21203/rs.3.rs-136612/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Auxiliary Rapid Identification of Pathogenic and Antagonistic Microorganisms for Coptis Chinensis Root Rot by High-throughput Sequencing

Abstract: Root rot reduced the yield and medical quality of C. Chinensis. Previous studies of Coptis root rot focused on the identification of pathogens and the rhizosphere microbial community composition. In order to provide more evidence for preventing this disease, the present study was to identify the pathogenic and antagonistic microorganisms based on a high-throughput sequencing technique. The healthy and diseased C. chinensis in the endosphere and rhizosphere from the same field were collected to investigating th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 54 publications
(63 reference statements)
1
0
1
Order By: Relevance
“…The fungal α -diversity in control Group “C” was more abundant than that in treatment Group “A,” but the bacterial diversity was lower. This is opposite to the results of the study on C. chinensis , in which the α diversity of the rhizosphere fungi of the diseased plants was significantly higher than that of the healthy plants, and the α diversity of the bacteria in the endosphere of the diseased plants was significantly higher than that of the healthy plants ( Liao et al, 2020 ). This may be because the method of selection and drying could reduce the fungi brought into the cellar and reproduce in the cellar.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The fungal α -diversity in control Group “C” was more abundant than that in treatment Group “A,” but the bacterial diversity was lower. This is opposite to the results of the study on C. chinensis , in which the α diversity of the rhizosphere fungi of the diseased plants was significantly higher than that of the healthy plants, and the α diversity of the bacteria in the endosphere of the diseased plants was significantly higher than that of the healthy plants ( Liao et al, 2020 ). This may be because the method of selection and drying could reduce the fungi brought into the cellar and reproduce in the cellar.…”
Section: Discussioncontrasting
confidence: 99%
“…Further analysis of the functional groups of the fungal community revealed that the plant–pathogens were also abundant in Group “C” of HY, MY and ZL, while the fungal species of Saprotroph were more abundant in HZ, such as soil Saprotroph, dung Saprotroph and plant Saprotroph, etc. This result is consistent with reports of Coptis Chinensis in which the plant pathogens in the rhizosphere of diseased plants were significantly higher than those of healthy plants ( Liao et al, 2020 ). Therefore, these fungi may be the main pathogens of potato and the treatment were significantly reduced the distribution of pathogens.…”
Section: Discussionsupporting
confidence: 93%